2020
DOI: 10.1007/s10067-020-05328-5
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease in siblings in close temporal proximity to each other—what are the implications?

Abstract: Kawasaki disease (KD) is the commonest medium vessel vasculitis in children. The etiology of KD remains an enigma despite extensive research. Infections are considered to be one of the triggers for KD, especially in genetically susceptible hosts. KD occurring within a short time interval among siblings is an important clinical observation supporting this hypothesis. In addition, siblings of children with KD are at a higher risk of developing the disease as compared with other children. Screening for KD in febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…KD occurring within a short interval among sibling children is an essential clinical observation supporting this hypothesis [27]. However, of the >201 sibling pairs reviewed, a specific infectious trigger was documented in only five pairs, which included streptococcus, adenovirus, parvovirus, varicellazoster virus, and measles virus [27]- [29]. In the present study, a specific infectious trigger was not documented in sibling pair number 3 with a 7-day interval (Table I).…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…KD occurring within a short interval among sibling children is an essential clinical observation supporting this hypothesis [27]. However, of the >201 sibling pairs reviewed, a specific infectious trigger was documented in only five pairs, which included streptococcus, adenovirus, parvovirus, varicellazoster virus, and measles virus [27]- [29]. In the present study, a specific infectious trigger was not documented in sibling pair number 3 with a 7-day interval (Table I).…”
Section: Discussionsupporting
confidence: 47%
“…Infections are considered to be a trigger for KD, especially in genetically susceptible hosts [27]. KD occurring within a short interval among sibling children is an essential clinical observation supporting this hypothesis [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…J o u r n a l P r e -p r o o f by Dr Tomisaku Kawasaki in 1967. 11 Previous studies strongly support that infectious agents trigger an abnormal acute immune response of KD, according to epidemiologic characteristics such as the age distribution, with the highest susceptibility among children aged <2 years and lowest in those aged <6 months, compatible with infection by a ubiquitous agent resulting in increasing immunity with age and with transplacental immunity; [1][2][3][4][12][13][14] occurrence through potential sibling-to-sibling transmission inside households; 13,[15][16][17][18] temporal-and municipallevel clustering; [19][20][21] seasonal difference in occurrence; [21][22][23][24][25][26] ; and epidemics observed during the past 50 years in Japan (1979, 1982, and 1986). [1][2][3][4] Recent studies have reported that the incidence of KD decreased during the coronavirus disease 2019 (COVID-19) pandemic period compared with the corresponding period in previous years.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on KD in siblings [ 16 , 17 , 18 ], the interval of the onset of KD in two sibling patients peaked on the same day and at less than a week to one month, suggesting the involvement of a KD trigger that mostly occurred within a 7-day incubation period and occasionally occurred within a 28-day incubation period. We, therefore, defined the “case period” as 7 days (S) or 28 days (L) before the date of the onset of KD.…”
Section: Methodsmentioning
confidence: 99%